Balancing financial sustainability and affordability in public transport: The case of Bogota, Colombia - Camila Rodríguez Hernández; Tatiana Peralta-Quiros (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
In order to meet the challenges of providing affordable public transit services for the urban poor and at a cost that doesn't impinge on the system's financial sustainability, cities can consider setting fares at "cost recovery" levels for the majority of the population and targeting subsidies to those who need them most. Bogotá is a case in point - the new public transport system was designed so fares are set close to "cost recovery" levels to aim for greater financial sustainability. To provide affordable services, the city leveraged the adoption of smartcards in its new public transit system and the country's poverty targeting instruments to implement a pro-poor public transit subsidy. This paper presents a critical analysis of Bogotá's experience with trying to balance financial sustainability and affordability. The paper describes some of the features of Bogota's tariff policy, namely, the concept of tariff set at "cost recovery" levels and lessons learnt in trying to achieve financial sustainability. The paper also lays out the rationale, design and implementation of Bogota's pro-poor public transit subsidy, and the subsidy's impact on its beneficiaries.
Keywords: 330; Kommunalhaushalt; Nachhaltigkeit; Armutsbekämpfung; Öffentlicher Nahverkehr; Fahrpreis; Bogota; Kolumbien